2003
DOI: 10.1007/s00406-003-0399-4
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime depressive and somatic symptoms as preclinical markers of late-onset depression

Abstract: Different symptoms can be used individually and in combination to predict later depression. This might allow early treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 45 publications
0
18
1
Order By: Relevance
“…Most data suggest chronic pain predisposes patients to the emergence of depression [3••, Class I]. For example, among elderly patients, the presence of joint pain was one of the most significant predictors of incident depression at 5-year follow-up [8,Class II]. Conversely, depression can predict future pain.…”
Section: Opinion Statementmentioning
confidence: 98%
“…Most data suggest chronic pain predisposes patients to the emergence of depression [3••, Class I]. For example, among elderly patients, the presence of joint pain was one of the most significant predictors of incident depression at 5-year follow-up [8,Class II]. Conversely, depression can predict future pain.…”
Section: Opinion Statementmentioning
confidence: 98%
“…Data are in favor of adding the existence of physical symptoms to the current criteria rather than to oppose them to psychologic symptoms. The presence of somatic symptoms of depression actually predicts the onset of a further episode of depression [23].…”
Section: "Diagnosis Is Hidden Because Of a Physical Presentation Of Smentioning
confidence: 99%
“…However, this may be explained by the possibility that depression in a community sample is less likely to be complicated by factors such as comorbid vascular disease. Hein et al (2003), in a 2-year prospective follow-up study, identified lifetime depressive and somatic symptoms as preclinical markers of late-onset depression. Certain symptoms, when present for over 2 weeks at any age, individually predicted lateonset depression.…”
Section: Vascular Diseasementioning
confidence: 99%